Assessment of effectivity of design models for sewerage and drainage systems - Mamoon, Abdullah Al; Orth, H.M.; I, Fude; Hanaki, K.; The Royal Netherlands Government (Bangkok : Asian Institute of Technology, 1986)
The efficiency of computer based modelling is assessed by testing the Dynamic programming model developed at AIT by SROIKEEREE (1985) on microcomputers. considering elevation. pipe diameter and time of flow as state variables. The model is applied to some large and small real networks simulating actual field conditions. Capital cost savings of 2.10 - 7.7 % were found by using model design rather than convetiona1 design. Inclusion of time of flow as a state variable reduced cost to about 1 % more than compared to those from models considering only elevation and diameter. Behavior of the model seems to be dependent mostly on topographic conditions. Introducing the diameter into the state variables reduced least-cost by about 17 % in an artificial network. The model is capable of designing storm. sanitary and combined systems effectively and its operation does not require much skill. One important feature of this model is the use of microcomputers which could be readily available specially in developing countries and can be easily installed in design offices engaged in sewer system design. Besides this. the model also showed sensitivity to maximum and minimum velocity. sewer cover and cost functions etc. Results obtained from this study demonstrate the great likelihood of the acceptance of model based design by sewerage and drainage engineers instead of conventional design.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1986
Keywords: Dynamic programming; Drainage